Walking Tour sebagai Strategi Pengembangan Wisata Perkotaan - Lintang Annisa (Warta Pariwisata, 2023)
Walking tour is a fundamental tourism activity. Nowadays, it develops along with the shifting tourism pattern from fast tourism to slow tourism. This journal analyzes the definition of walking tour as well as its benefits as the development strategy of urban tourism. The literatures review contributes to define the walking tour, types of walking tour, and the concept of walking tour to be further taken into consideration in developing the urban tourism